Dasar Hukum dan Regulasi Perbankan Syariah di Indonesia - Khairun Nisaa; Rozi Andrini (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article explores the development of Islamic banking in Indonesia, starting with the establishment of Bank Muamalat in 1992. It highlights the growing public demand for a banking system that is in accordance with Islamic principles and discusses the importance of the regulatory framework in ensuring operational legal certainty, consumer protection, and national financial stability. The hierarchy of the legal basis for Islamic banking in Indonesia is examined, including constitutional provisions, relevant laws, and technical regulations. The article concludes with recommendations for regulatory improvement and suggestions for industry growth, emphasizing the need for education, innovation, and collaboration among financial institutions.